ANALYSIS AND DESIGN OF FINANCIAL STATEMENT ACCOUNTABILITY MANAGEMENT INFORMATION SYSTEM - Khan, Najeeb Ullah; Putri, Gita Leviana (Asia Information System Journal, 2023)
This research conducted in Lampung Province, Indonesia, aims to investigate the factors influencing the issuance of opinions on the financial statements of district governments. The study utilizes interviews processed through to analyse and design of  the Financial Statement Accountability Management Information System (SIMALK) application to analyze the impact of technology utilization and oversight on financial reporting. Findings reveal that the Reasonable Without Exception (WTP) opinion by BPK RI is supported by the internal control system within SIMALK and oversight by the Inspectorate, rather than the presence of the SPI. The flowchart of SIMALK illustrates a systematic data processing and decision-making workflow. Financial supervision involves audits by district and provincial inspectorates, ensuring compliance with budgetary allocations and financial accountability. The study underscores the importance of public sector financial reporting in promoting transparency and accountability, highlighting the need for continuous training, technological infrastructure, and commitment from local governments to enhance governance practices and stakeholder trust.